2014
DOI: 10.1017/s0266462314000439
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Bypass Surgery Versus Percutaneous Coronary Intervention: Cost-Effectiveness in Iran: A Study in Patients With Multivessel Coronary Artery Disease

Abstract: This study demonstrated that despite higher initial cost and lower HRQoL, CABG is a cost-effective revascularization strategy compared with PCI for patients with multivessel coronary artery disease in long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Our results reveal that in the short-term, CABG costs less than PCI and has a better prognosis among CAD patients with stable triple-vessel or left-main. This result of the study was consistent with some randomized clinical trials (RCT) and observational studies reported by previous economic and clinical outcomes [13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…Our results reveal that in the short-term, CABG costs less than PCI and has a better prognosis among CAD patients with stable triple-vessel or left-main. This result of the study was consistent with some randomized clinical trials (RCT) and observational studies reported by previous economic and clinical outcomes [13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, patients selected for both procedures are not representative of multivessel disease because 41% of them had single-vessel disease and just 8% were triple-vessel disease patients [ 20 ]. More recently, a study was carried out by the Iran society perspective to evaluate PCI with stents versus CABG in patients with triple-vessel disease [ 21 ]. Contrary to our findings, it found that CABG is a cost-effective strategy compared with PCI, whereas this study included a small and unbalanced sample size, and cardiovascular events were not included in the Markov model over 5 years, 10 years, and life-time horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, it found that CABG is a cost-effective strategy compared with PCI, whereas this study included a small and unbalanced sample size, and cardiovascular events were not included in the Markov model over 5 years, 10 years, and life-time horizon. Instead, it used a specific questionnaire to measure QALY, which makes it difficult to compare with other studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary bypass surgery (CBAG) in patients with multi-vessel coronary artery disease [28] and, tissue plasminogen activator in patients with ischemic stroke [29] are cost effective interventions from society and thirdparty perspective, respectively. Moreover, homograft valve in patients that underwent homograft and mechanical heart valve replacement surgery is a cost effective intervention [30].…”
Section: Coronary Artery Diseasementioning
confidence: 99%